2004
DOI: 10.1177/030857590402800105
|View full text |Cite
|
Sign up to set email alerts
|

Group Work for Foster Carers Caring for Children with Complex Problems

Abstract: Group work provides foster carers with an important means of receiving support and psycho-education. It gives them opportunities to explore different ways of understanding and managing foster children. Kim Golding and Wendy Picken describe the use of two different types of groups developed by the Primary Care and Support Team in Worcestershire. The first is based on a parent-training programme. Group facilitators help carers to consider different management techniques and think about their use with the complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 17 publications
3
71
0
Order By: Relevance
“…However, as indicated above, almost half of the original sample did not complete treatment. Foster parents receiving the IY parent training intervention were more satisfied than those having the Fostering Attachments intervention in the study by Golding and Picken, 511 with 84% saying that they found the programme to be very helpful, compared with 60% in the fostering attachment group. Only half of each intervention group stated that they had some increase in their understanding and confidence.…”
Section: Caregivers' Viewsmentioning
confidence: 90%
See 4 more Smart Citations
“…However, as indicated above, almost half of the original sample did not complete treatment. Foster parents receiving the IY parent training intervention were more satisfied than those having the Fostering Attachments intervention in the study by Golding and Picken, 511 with 84% saying that they found the programme to be very helpful, compared with 60% in the fostering attachment group. Only half of each intervention group stated that they had some increase in their understanding and confidence.…”
Section: Caregivers' Viewsmentioning
confidence: 90%
“…The remainder were in Canada (four studies 170,[658][659][660][661] ), the UK (14 studies 145,169,481,511,538,[662][663][664][665][666][667][668][669][670] ) and elsewhere in Europe: the Netherlands (three studies 497,671,672 ), Norway (three studies [673][674][675] ) and Sweden (one study 676 ), with one multisite review of services 145,146,640,[665][666][667][668][669][670] across Italy, the Netherlands and the UK. A small number of studies were based outside North America and Europe: Australia (two studies 506,677 ), Brazil (one study 678 ), India (one study 679 ) and the Philippines (one study 680 ).…”
Section: Description Of Included Acceptability Studiesmentioning
confidence: 99%
See 3 more Smart Citations